Unraveling late Pennsylvanian brachiopod assemblages from the San Rafael Basin (Argentina): Biostratigraphic implications to southwestern Gondwana - Taboada, Arturo Cesar (2021)
New and previous fossil remains and resulting biostratigraphy of the El Imperial Formation at Arroyo del Imperial, Quebrada de La Horqueta, and Can˜on ´ del Atuel key sections are analyzed, while the faunal relationships among them are clarified. Two diachronnous faunas, the pTS and TSAIII associations, relatives to the TivertoniaStreptorhynchus assemblage are recognized and constrained to early late Bashkirian and Moscovian ages, respectively. These age assignments are supported by statistical analyses and available palynological and radiometric dating. Previous mentions of brachiopods from Arroyo del Imperial and Quebrada de La Horqueta are elucidated with the identification of Buxtonia cf. riojanae (Leanza), Streptorhynchus inaequiornatus Leanza, Spiriferellina? sp., Septosyringothyris (Precosyringothyris) aff. jaguelensis Lech, Septosyringothyris (Precosyringothyris) cf. feruglioi (Amos), Saltospirifer guevarai Cisterna and Archbold and Pericospira sp. A new marine fauna from the upper part of the Can˜on ´ del Atuel section (Cabecera del Can˜on ´ Member) is reported. It includes the brachiopods Argentiella cf. A. stappenbecki Archbold, Cisterna and Sterren, Oehlertella annae (Feruglio), Orbiculoidea saltensis Reed, Calytrixia piersoni Taboada, Coolkilella aredesi Taboada, Costatumulus sp. and Septosyringothyris? sp. A biochronostratigraphic correlation scheme, including key lithostratigraphic units and biozones of central-western Argentina is updated.